Reflecting on Reflections on COVID-19 - Ynte K. Van Dam; Joke F. Webbink (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper is an invited reaction to Platje, Harvey & Rayman-Bacchus, March 2020, 'COVID-19 - reflections on the surprise of both an expected and an unexpected event' in CEREM 4(1). In the tradition of critical science this paper starts from a discussion of the assumptions underlying the paper it reacts upon. ~ Findings: The original text is a laudable attempt to initiate a discussion on unpredictable future threats that remains constricted in semantic confusions, misperceptions, misinterpretations, and logical fallacies implying preconceived conclusions. As a logical consequence of a socio-economic system that systematically disregards human wellbeing and welfare - and exploits human weaknesses - in its endless pursuit of short term profit, the current pandemic and its subsequent crisis was expected and predictable, but wilfully ignored. And, unless this crisis will be used to rebuild the socio-economic system for sustainable development, so will be the next one.
Keywords: 330; COVID-19; Economy; Psychology; Sustainable Development